Second-Hand Gentrification: Theory and Evidence from High-Speed Rail Extensions - Gabriel Loumeau; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates whether and how gentrification spreads along intercity transport connections. We consider a model with heterogeneous individuals populating a primary and a secondary city, with commuting within and between cities. By reducing the cost of intercity commuting, the HSR connection induces migration by skilled individuals towards the secondary city. Therefore, house prices rise in the secondary city, and unskilled individuals are pushed to its periphery. We call this effect second-hand gentrification. We confirm these predictions using the 2017 expansion of the French HSR network from Paris to Bordeaux and Rennes. We find that the HSR connection made skilled Parisians more likely to move to Bordeaux and Rennes, that these individuals locate over-proportionally in central locations of such cities, and that housing prices there consequently increased by exteuro400 per m2 (i.e., 7%). Remarkably, we also find a negative effect on prices in Paris.
Keywords: R23; R11; R41; 330; gentrification; high speed rail; housing market; Intercity travel